Loss of retinal nerve fibre layer axons indicates white but not grey matter damage in early multiple sclerosis. Issue 5 (31st January 2013) - Young, K. L.; Brandt, A. U.; Petzold, A.; Reitz, L. Y.; Lintze, F.; Paul, F.; Martin, R.; Schippling, S.
<x xml:space="preserve">Abstract</x> Background and purpose Optical coherence tomography (OCT) has shown thinning of the retinal nerve fibre layer (RNFL) and total macular volume (TMV) in multiple sclerosis (MS) patients. Measures of retinal atrophy are associated with the brain parenchymal fraction (BPF) assessed by magnetic resonance imaging (MRI). However, in MS, data on the relation of OCT measures and grey and white matter volumes are contradictory. We performed a prospective cross‐sectional study with a statistically pre‐defined endpoint to test our hypothesis that OCT measures of neuro‐axonal degeneration are related to global and partial brain atrophy in early forms of MS. Methods and results Forty‐four patients with clinically isolated syndrome (n = 10) or relapsing–remitting MS (n = 34; mean disease duration = 3.2 years, median EDSS = 1.5) were enrolled in the study. Peripapillary‐ and volumetric OCT scans of the macula were performed using latest spectral‐domain OCT technology. BPF as well as white and grey matter fractions (WMF/GMF) were assessed by 1.5 Tesla MRI scans. Generalized estimating equation models adjusted for age and linear regression statistics were used to assess the association between OCT and MRI measures. RNFL thickness, TMV and age were significantly associated with BPF. RNFL thickness and TMV independently predicted WMF (P = 0.003 and P = 0.032) but not GMF (P = 0.717 and P = 0.357) when corrected for age. In contrast, age was strongly associated with GMF (P < 0.001) but not WMF. Conclusion Our study suggests that, in early MS, OCT measures of retinal atrophy are related to volumetric changes in the white but not grey matter compartment as assessed by MRI. It further substantiates the association of retinal thinning and brain tissue loss in MS.